Ethics of Du Pont's CFC Strategy 1975–1995 - Smith, Brigitte (Journal of business ethics, 1998)
The ethics of Du Pont's CFC strategy from 1975 to 1995 are analyzed using a Potter's Box framework. This approach includes an examination of relevant facts, prioritization of stakeholder loyalties, selection of a mode of ethical reasoning, and a world view. Du Pont's approach to ethical reasoning reflects changing facts and changing interpretation of the facts, a focus on shareholders as the primary and most important stakeholder, and ends-based reasoning, which views creating shareholder value as the primary end. An alternative approach is proposed, based on analysis of Du Pont's and stakeholders' needs.